CBLC inhibits the proliferation and metastasis of breast cancer cells via ubiquitination and degradation of CTTN. (2nd November 2022) - Li, Weiwei; Lei, Ting; Song, Xiaoyu; Deng, Chun; Lu, Jingrun; Zhang, Wenwu; Kuang, Zhenzhan; He, Yongyin; Zhou, Quan; Luo, Zhaoxun; Mo, Fei; Yang, Hanlin; et al.
Abstract: The E3 ubiquitin ligase is an important regulator of cell signaling and proteostasis and is tightly controlled in many diseases, including cancer. Our study aimed to investigate the biological role of the E3 ubiquitin ligase CBLC in breast cancer and elucidate the specific mechanistic network underlying CBLC-mediated target substrate degradation, cell proliferation and metastasis. Here, we showed that CBLC expression was higher in breast cancer tissues and cells than that in normal tissues and cells. Higher expression of CBLC predicted a better prognosis for breast cancer patients. CBLC inhibited the proliferation, migration and invasion of breast cancer cells. Co-IP and immunofluorescence co-localization assays demonstrated that CBLC interacted with CTTN in the cytoplasm. CBLC promoted the degradation of CTTN through the ubiquitin-proteasome pathway without affecting its mRNA level. The inhibitory effect of CBLC on breast cancer cell proliferation, migration and invasion could partly be reversed by CTTN. Taken together, our study clarified the biological role of CBLC as a tumor suppressor and discovered its functional substrate, providing a molecular basis for CBLC/CTTN as a potential therapeutic target in breast cancer.